UPAYA MENINGKATKAN KETERAMPILAN MENGAJAR GURU MELALUI KEGIATAN LESSON STUDY DI SD NEGERI BUMIHARJO - Suryani, Rini (Information Technology Education Department, 2022)
Efforts to increase teacher competence need to be made to help improve professionalism in teaching. The number of success factors is because the teacher's skills in delivering teaching materials and materials can encourage students to be motivated in the learning process. Although skills are basic things that must be possessed by teachers, there are still some obstacles including, teachers are not able to manage the class, teachers have not been able to provide reinforcement to students, teachers have not been able to control the atmosphere in the classroom and teachers often miss activities in a series of closing the learning process. If this condition continues, it can affect student learning activities. Therefore, a school action research (PTS) was conducted through a lesson study to see the improvement of the teaching skills of teachers, especially at SD Negeri Bumiharjo. The research subject is the competence of teachers in SD Bumiharjo with qualitative and descriptive comparative data collection. The results of the study indicate that efforts to improve the teaching skills of teachers have increased through lesson study activities at SD Negeri Bumiharjo.